2020
DOI: 10.22452/jdbe.vol20no3.2
|View full text |Cite
|
Sign up to set email alerts
|

Building Information Modelling (BIM) Adoption Model for Architectural Education

Abstract: The purpose of this study is to design a Building Information Modelling (BIM) integration model for architectural education in adopting BIM culture. Most of the current models on BIM adoption are directed toward the realm of construction industries (consultant firms and contractors) and less on higher education institutions. The discourse on education is mostly concerning experimentation on curricular integration and the lack of general concepts of integration. The main research inquiry of this study is concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…BIM has led to the dependency on technological usage to manage data for delivery and collaboration between construction parties (Ismail et al, 2019). However, the interest and awareness of BIM and its implementation in practice and academia vary significantly from country to country (Maharika et al, 2020). Thus, the Malaysian government has highly encouraged the application of BIM to transform the Malaysian construction industry to a higher level.…”
Section: The Benefits Of Implementing Bim For the Aec Professionmentioning
confidence: 99%
See 3 more Smart Citations
“…BIM has led to the dependency on technological usage to manage data for delivery and collaboration between construction parties (Ismail et al, 2019). However, the interest and awareness of BIM and its implementation in practice and academia vary significantly from country to country (Maharika et al, 2020). Thus, the Malaysian government has highly encouraged the application of BIM to transform the Malaysian construction industry to a higher level.…”
Section: The Benefits Of Implementing Bim For the Aec Professionmentioning
confidence: 99%
“…A study conducted by (Maharika et al, 2020) found that most of the current models on BIM adoption are directed toward the area of construction industries (consultant firms and contractors) and less toward higher education institutions, mainly concerning experimentation on curricular integration and the lack of general concepts of integration. Zhang et al…”
Section: The Barriers To Implementing Bim In Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…On top of these, the vision and mission of the institution must also support a dynamic paradigm of pedagogical changes to incorporate the needs of the ever-evolving built environment industry. (Fadjar Maharika et al, 2020). Another issue is a lack of study on how to effectively integrate the course that deals with environmental BIM analysis in architecture education within the existing curriculum.…”
Section: The Significance Of Environmental Bim Analysis In Architectu...mentioning
confidence: 99%